NEW SYSTEM IN CRIMINAL PROCEEDINGS AGAINST VILLAGE HEADS FOR CORRUPTION OF VILLAGE FUNDS - Surya Hamdani; Saritua Silitonga; Sarah Furqoni; Muhammad Dhobit Azhary Lubis (Sean Institute, 2023)
Decision number 168 k/pid.sus/2018 on behalf of the defendant kabul santosa bin wito diharjo was proven legally and convincingly guilty of committing the crime of